2023
DOI: 10.1021/jacs.3c08257
|View full text |Cite
|
Sign up to set email alerts
|

From Helices to Crystals: Multiscale Representation of Chirality in Double-Helix Structures

Chong-Yang Li,
Han Xu,
Pei-Ming Cheng
et al.

Abstract: Single crystals with chiral shapes aroused the interest of chemists due to their fascinating polarization rotation properties. Although the formation of large-scale spiral structures is considered to be a potential factor in chiral crystals, the precise mechanism behind their formation remains elusive. Herein, we present a rare phenomenon involving the multitransfer and expression of chirality at micro-, meso-, and macroscopic levels, starting from chiral carbon atoms and extending to the double-helical second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…This partly slow growth of crystal face families {(−1 0–1) (−1 0 1), (1 0 1), (1 0–1)} and fast progress of {(−1 1 0), (−1–1 0), (1 1 0), (1–1 0)} facilitate D 2h symmetry of the dodecahedron (Figure S52). Thus, the actual dodecahedron geometry of the crystals results from an integration of intrinsic homochiral features and differential growth rates. , Based on the sight of the crystallographic molecular structure, SEGPHOS and its fluoro-analogs SEGPHOS-CF2 have a similar spatial configuration and bonding parameters, in which SEGPHOS and SEGPHOS-CF2 exhibit dihedral angles (θ) of 76.6 and 79.6° between two 4,4′-bibenzo­[ d ]­[1,3]­dioxole parts, respectively. The trigonal P­(III) centers are distorted due to subtle noncovalent interaction effects (NCIs) in both intermolecular and intramolecular disturbances (Figure a and Figure S34), i.e., the centroid contact could be noticed with 3.96 Å between phenyl and dioxole (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…This partly slow growth of crystal face families {(−1 0–1) (−1 0 1), (1 0 1), (1 0–1)} and fast progress of {(−1 1 0), (−1–1 0), (1 1 0), (1–1 0)} facilitate D 2h symmetry of the dodecahedron (Figure S52). Thus, the actual dodecahedron geometry of the crystals results from an integration of intrinsic homochiral features and differential growth rates. , Based on the sight of the crystallographic molecular structure, SEGPHOS and its fluoro-analogs SEGPHOS-CF2 have a similar spatial configuration and bonding parameters, in which SEGPHOS and SEGPHOS-CF2 exhibit dihedral angles (θ) of 76.6 and 79.6° between two 4,4′-bibenzo­[ d ]­[1,3]­dioxole parts, respectively. The trigonal P­(III) centers are distorted due to subtle noncovalent interaction effects (NCIs) in both intermolecular and intramolecular disturbances (Figure a and Figure S34), i.e., the centroid contact could be noticed with 3.96 Å between phenyl and dioxole (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15][16] Coordinationdriven self-assembly can simulate the self-recognition process among chiral template units of different configurations, providing new research ideas for simplifying and simulating the formation of complex chiral macromolecules having multilevel structures from simple primitives in living organisms. [17][18][19][20] In addition, chiral lanthanide complexes show attractive application prospects in the fields of enantioresolution, molecular recognition, nonlinear optics and asymmetric catalysis. In 2017, Cui et al reported a chiral porous octahedral cage that can serve as an efficient asymmetric supramolecular catalyst to achieve high catalytic activity and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…22 In 2023, Kong et al used amino acid amide groups and complexes of Ni 3+ and lanthanide metals as basic building blocks to assemble into a DNA-like chiral double helix structure driven by coordination bonds and hydrogen bonds, achieving the goal of chirality transfer from microscopic to mesoscopic scales. 17 The controllable preparation of chiral lanthanide complexes is extremely challenging due to the large ion radius, variable coordination number, diverse coordination modes, and easy distortion of the coordination sphere of lanthanide metals. 23–29 Despite these difficulties, we have made some progress in the directional construction of chiral lanthanide clusters having specific shapes and structural connections and their self-assembly mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…French chemist Louis Pasteur managed to manually separate the racemic mixture of single crystals of ammonium sodium tartrate tetrahydrate with tweezers in 1848 by carefully discerning the discrepancies in their morphologies (Figure ). , This experiment marks the first artificial chiral resolution in the history of science and technology and simultaneously also lays the foundation for what we now call stereochemistry. , How the chirality of molecules affects the overall properties and functionalities of the crystal in an easily observed way, preferably with the naked eye, has rarely been considered as an independent issue before but worth thinking. However, in this contribution, we conceived a unique dynamic molecular system based on the racemic mixture of asparagine monohydrate. When heated at specific faces, crystals consisting of the opposite enantiomers jump macroscopically toward the opposite directions, which could be further utilized to achieve the mechanical separation of the racemic mixtures (Figure ).…”
Section: Introductionmentioning
confidence: 99%